2006
DOI: 10.1093/chemse/bjj031
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Modal Interactions Between Olfaction and Touch

Abstract: We report two experiments designed to investigate the nature of any cross-modal interactions between olfactory and tactile information processing. In Experiment 1, we assessed the influence of olfactory cues on the tactile perception of fabric softness using computer-controlled stimulus presentation. The results showed that participants rated fabric swatches as feeling significantly softer when presented with a lemon odor than when presented with an animal-like odor, demonstrating that olfactory cues can modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(107 citation statements)
references
References 45 publications
6
95
2
Order By: Relevance
“…The fragrance-free cream formulation was also considered the greasiest among the cream formulations according to ten testers. These results corroborated those of Dermatte et al (2006) who correlated the sense of touch with the sense of smell and demonstrated the existence of a cross-modal interaction between olfaction and touch. These authors also mentioned that there were effects exerted by stimuli presented in one sensory modality on people's responses to stimuli presented in another modality could be due to a process of associative learning.…”
Section: Cr) Cream Formulations; (G) Gel Formulations; (A) Sweet Florsupporting
confidence: 88%
“…The fragrance-free cream formulation was also considered the greasiest among the cream formulations according to ten testers. These results corroborated those of Dermatte et al (2006) who correlated the sense of touch with the sense of smell and demonstrated the existence of a cross-modal interaction between olfaction and touch. These authors also mentioned that there were effects exerted by stimuli presented in one sensory modality on people's responses to stimuli presented in another modality could be due to a process of associative learning.…”
Section: Cr) Cream Formulations; (G) Gel Formulations; (A) Sweet Florsupporting
confidence: 88%
“…However, it is evident from gestalt principles that the sensory input from the environment is not simply perceived as the sum of its individual components, but rather as a whole (Lin, 2004). Experiments conducted in laboratory settings show that there is a broad spectrum of non-linear interactions between all sensory modalities (Bresciani et al, 2005;Demattè, Sanabria, Sugarman, & Spence, 2006;Driver & Noesselt, 2008;Seigneuric, Durand, Jiang, Baudouin, & Schaal, 2010;Shimojo & Shams, 2001;Small, 2004;Thesen, Vibell, Calvert, & Österbauer, 2004). This means that when cues from different sensory modalities are integrated, the result is not a simple accumulation of the effects generated by each modality separately.…”
Section: Introductionmentioning
confidence: 99%
“…14 In other, yet highly relevant research fields, the examination of synesthetic characters has recently attracted attention under the label of crossmodal correspondence, for example the crossmodal correspondence between olfaction and touch (Demattè, Sanabria, Sugarman et al, 2006), odors and music (Crisinel & Spence, 2012), odors and shape (Hanson-Vaux, Crisinel & Spence, 2013) or taste and music (Crisinel, Cosser, King et al, 2012). Other terms to refer to similar phenomena include synaesthetic correspondences, synaesthetic associations, crossmodal equivalences, crossmodal similarities, and natural crossmodal mappings (Spence, 2011).…”
Section: Ambiances Variamentioning
confidence: 99%